IMPLIKASI TERHADAP REALITA PERKEMBANGAN BUSANA ADAT KE PURA BAGI REMAJA HINDU - Kartika, Ni Gusti Ayu (Institut Hindu Dharma Denpasar, 2018)
The phenomenon of celebrity appearance which is now hitting Hindus is an empirical reality whose direction of development is not easily rejected, moreover, to avoid. In connection with the phenomenon of the appearance of celebrities of Hindus, it is quite clear that the actions or behavior of the people by making the biological body as a media of aesthetization in the form of celebrity appearances laden with materialist-capitalistconsumerism (objects, money and consumptive style) with the aim of hedonists (enjoying pleasure) mundane). The era of modernization and globalization with its materialist consumerism lifestyle seems to have hypnotized Hindus to submit to all that is modern or posmo, even though it would actually lead to hedonism which only views life to enjoy solitary pleasures. This is the basis of the reduction in the ethics of life, not only in the world now but also in the world of noetic, especially those related to the ethics of religious life and the decreasing level of obedience or obedience to follow ethical norms or rules that must be used as guidelines or guidelines behave.